Singapore’s Education Concept: Comparative and Applicative Study to The Quality of Indonesia’s Education - Euis Eka Pramiarsih (Universitas Sebelas Maret, 2019)
Education is one of the most important components in life. Since man started educating themselves, since then man has managed to realize a wide range of development and progress in every part of their lives. In order to improve the quality of education in Indonesia, the government continues to make various reforms in the education sector. Indonesia's education system has advantages and disadvantages compared to other countries. Comparative studies of education systems is one way to find out various aspects related to the Indonesian education system with certain countries, especially those related to the advantages and disadvantages that occur in the education system. For this reason, on this occasion the author tries to review and describe the comparison of education between Indonesia and Singapore.